Implementasi Dana Alokasi Khusus (DAK) Non Fisik Kefarmasian di Kabupaten Purwakarta Tahun 2019 - M Arief Jatmiko; Hermawan Saputra; Abdullah Antaria; Desrialita Faryanti (Syntax Corporation Indonesia, 2022)
Non-physical DAK for pharmaceuticals is one of the APBN budgets given to districts/cities in the pharmaceutical sector with a menu of distribution of drugs, vaccines and medical consumables (BMHP) as well as support for the use of information systems or drug logistics applications and electronic BMHP as a government effort to guarantee availability of drugs in primary health services. The focus of this research is the implementation of non-physical DAK pharmaceutical BOK implementation policies at the Purwakarta District Health Office. The performance of policy implementation needs to be analyzed in order to evaluate to generate feedback for the next policy development process. Data collection techniques are through in-depth interviews with key informants, observation, and document review. This research uses the Van Meter and Van Horn policy implementation model approach. The results of the research show that it is still necessary to improve the understanding of implementers in planning activities and the low compliance of reporting on the realization of Non-physical DAK in accordance with the established technical guidelines